A Cost-Benefit Analysis of a Potential Supervised Injection Facility in San Francisco, California, USA. (April 2017) - Irwin, Amos; Jozaghi, Ehsan; Bluthenthal, Ricky N.; Kral, Alex H.
Supervised injection facilities (SIFs) have been shown to reduce infection, prevent overdose deaths, and increase treatment uptake. The United States is in the midst of an opioid epidemic, yet no sanctioned SIF currently operates in the United States. We estimate the economic costs and benefits of establishing a potential SIF in San Francisco using mathematical models that combine local public health data with previous research on the effects of existing SIFs. We consider potential savings from five outcomes: averted HIV and hepatitis C virus (HCV) infections, reduced skin and soft tissue infection (SSTI), averted overdose deaths, and increased medication-assisted treatment (MAT) uptake. We find that each dollar spent on a SIF would generate US2.33 in savings, for total annual net savings of US3.5 million for a single 13-booth SIF. Our analysis suggests that a SIF in San Francisco would not only be a cost-effective intervention but also a significant boost to the public health system.